Development and characterization of cassava bagasse (Manihot esculenta Crantz) and black seed (Nigella sativai L.) fiber filler corn (Zea mays L.) starch biocomposites - Abotbina, Walid A M. (2023)
The vast application of petroleum-based plastics had led to severe issues threatening the environment with numerous hazards such as accumulation of non-biodegradable plastic wastes and release of toxic gases through incineration. Researchers and scientists are in effort to develop eco-friendly materials that could rival the current petroleum-based plastic in terms of physical properties, mechanical strength, gas permeability and thermal stability. In this study, black seed (BS) fiber and cassava bagasse (CB) were used to reinforced corn starch-based polymer through the method of solution casting. Although studies have also been performed using corn starch as bioplastic, limited research has been reported in which BS and CB are reinforced with corn starch for solving the mechanical properties of bioplastics. A series of lab analysis were conducted to quantify the capabilities of the hybrid composites as packaging plastic. The physico-chemical properties of BS and CB were analyzed to understand the strengths and weaknesses in developing composites material. Both BS and CB indicated low cellulose content of 0.14% and 5.39%, respectively, which are beneficial to reduce the hydrophilicity of a composite. High number of lignin (65%) layers in BS is responsible to coat the cellulose hindering them to react with other molecules. The incorporation of 30% of fructose (F) and glycerol (G) into corn starch (CS) based polymer yield improved tensile strength, elongation at break, water absorption capacity and decomposition temperature. Fructose is good in improving mechanical and morphological properties meanwhile glycerol reduces the water sensitivity feature. CS/BS9% composite film exhibit optimum tensile strength and elastic modulus of 14.07 and 83.65 MPa, respectively. CS-BS/CB9% recorded a crystallinity value of 38.8± 2.1% compared to the control composite film (34.6 ± 1.6%). The tensile strength and elastic modulus were enhanced from 14.07 to 18.22 MPa and 83.65 to 118.32 MPa, respectively. Interestingly, a reduction in water absorption capacity but faster biodegradation rate during soil burial test were observed. The development of such fully biodegradable packaging films is important in the effort to address the ongoing environmental problems and gradually substitute the widely used conventional packaging materials.